2021
DOI: 10.1186/s40545-021-00319-6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease risk prevention services by pharmacists in Saudi Arabia: what do policymakers and opinion leaders think?

Abstract: Background Cardiovascular disease (CVD) is an emerging contributor to national morbidity and mortality in Saudi Arabia. CVD risk prevention services are limited, particularly with an over-utilised public health sector and an under-utilised and under-resourced primary care sector. Globally, there is evidence that community pharmacists can play a key role in CVD prevention within primary care. However, the perspectives of policymakers and opinion leaders are critical to successful translation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…4 In Saudi Arabia, NCDs overall account for approximately 73% of all mortality and CVD in particular is the main cause of death, accounting for approximately 37% of all NCD deaths. 5,6 Ischemic heart disease (IHD) and stroke are among the top 10 causes of death in the Middle East, with IHD ranking second and stroke ranking fourth in Saudi Arabia. 7 Several risk factors contribute to the development of CVD, a few of which are hypertension (HTN), diabetes mellitus (DM), hypercholesterolemia (HyCh), cigarette smoking, and obesity.…”
mentioning
confidence: 99%
“…4 In Saudi Arabia, NCDs overall account for approximately 73% of all mortality and CVD in particular is the main cause of death, accounting for approximately 37% of all NCD deaths. 5,6 Ischemic heart disease (IHD) and stroke are among the top 10 causes of death in the Middle East, with IHD ranking second and stroke ranking fourth in Saudi Arabia. 7 Several risk factors contribute to the development of CVD, a few of which are hypertension (HTN), diabetes mellitus (DM), hypercholesterolemia (HyCh), cigarette smoking, and obesity.…”
mentioning
confidence: 99%
“…This was correlated and supported by different studies. [26][27][28][29] Promoting healthy behaviours of the general public is a key population strategy for reducing its burden and this may also be the driving point to CPPs for actively engaging to deliver cardiovascular disease prevention and treatment.…”
mentioning
confidence: 99%
“…One possible solution to address this is to upgrade the capability of pharmacists to provide CVD preventive care. Above all, policymakers are in favor of empowering pharmacists to provide CVD preventive services and health promotion ( Almansour et al, 2021 ). This study provides a valuable insight into community and hospital pharmacists' knowledge, attitude and practice regarding CVD prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacists shall be actively involved in many programs, including monitoring CVD risk factors, optimizing medications, diseases and health care wellness, public health, educational consultations, and preventive care ( Alshahrani et al, 2020 , Newman et al, 2020 , Vigneshwaran et al, 2013 ). Much research has established pharmacists' involvement in preventing and controlling CVD ( Alavudeen et al, 2023 , Almansour et al, 2021 , Fahs et al, 2018 , Peletidi et al, 2019 ). A recent report confirmed that practicing community pharmacists in Saudi Arabia have considerable knowledge and understanding of CVD risk factors ( Sulaiteen et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%